Potensi korosivitas pada tanah endapan dataran banjir sungai Citarum di Karawang, Jawa Barat - Yanwar Yusup Rukmana; Muhamad Ridwan; Zufialdi Zakaria; Dicky Muslim; Nadhirah Seraphine (Universitas Riau, 2020)
Corrosion is the biggest problem for equipment that utilised metal, including infrastructure. Corrosion is degradation of metal quality due to the chemical reaction of a metal with the surrounding environment, including soil. Important indicators that contribute to the classification of the rate of corrosivity in soils are water content, pH, types of minerals, soil resistivity values and other chemical-physical parameters. The research area is in Anggadita Village, Klari District, Karawang Regency, West Java Province. Drilling and sampling locations are approximately 300 meters from the Citarum river. The article aimed to investigate between physical and chemical characteristics (soil texture, type of resistivity, pH) of weathered sediments of the Citarum river flood plain to the classification of soil corrosivity. Soil classification in the study area is fine grained and classified into silt with high plasticity (MH-ML) and clay with high plasticity (CH). The results of the analysis of the distribution of potential soil corrosivity in the study area indicate that the level of soil corrosivity is at a high level of corrosive to very high corrosive